(untitled) (GEON Journal (Management, Organizations and Business), 2016)
The research was realized in the main supermarkets at the Bucaramanga City, started from the theoretical concepts. For data collection, were used qualitative and quantitative techniques at the chosen supermarkets, and then analyzes the results obtained and concludes with the construction to conceptual model with the correspondent statistic validation. It was analized the main factors present in point of sale which affect in the purchase decision making. Behavior consumer is contrasted with the proposed point of sale and the brands to attract attention or customers. Finally, it intends a model that highlights key elements to made decisions at the point of sales, such as the decor of the place, sales promoters, and the kind of advertising or visual merchandising. The results lead to the conclusion that 28% of the customers always make decisions by effect to the visual advertising or the visual merchandising, getting even to the 61%, considering those who change their decision occasionally.